2003
DOI: 10.1002/ijc.11011
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of both mucins and proteoglycans in cell‐cell dissociation and invasiveness of colon carcinoma HT‐29 cells

Abstract: Key words: colon carcinoma cells; E-cadherin; mucins; heparan sulfate proteoglycansEpithelial E-cadherin, a component of the adherens junctions, is crucial for the organization and maintenance of differentiated epithelia. 1 The extracellular NH2-terminal domain of this transmembrane glycoprotein mediates cell-cell adhesion in a homophilic and Ca 2ϩ -dependent way. The COOH-terminal domain binds to the actin cytoskeleton via ␣-catenin and ␤-catenin or plakoglobin. 2 Studies in cancer cell lines have shown that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 49 publications
3
39
0
Order By: Relevance
“…These results reveal a new link between GLI1 and E-cadherin/b-catenin signaling, and this interaction might mechanistically account for the fact that MUC5AC is a biomarker for poor prognosis in PDA patients. Indeed, Truant et al previously reported that MUC5AC attenuated E-cadherin-mediated cellcell adhesion in human colon cancer HT29 cells (Truant et al, 2003), which supports our present study. Does this finding mean that MUC5AC per se promotes the malignant behavior of cancer cells?…”
Section: Gli1-induced Muc5ac Attenuates E-cadherinsupporting
confidence: 93%
“…These results reveal a new link between GLI1 and E-cadherin/b-catenin signaling, and this interaction might mechanistically account for the fact that MUC5AC is a biomarker for poor prognosis in PDA patients. Indeed, Truant et al previously reported that MUC5AC attenuated E-cadherin-mediated cellcell adhesion in human colon cancer HT29 cells (Truant et al, 2003), which supports our present study. Does this finding mean that MUC5AC per se promotes the malignant behavior of cancer cells?…”
Section: Gli1-induced Muc5ac Attenuates E-cadherinsupporting
confidence: 93%
“…In contrast to HT-29 cells which are drug-sensitive and undifferentiated (15,16), the drugresistant HT29-5F7 and HT29-5M21 clones exhibited differentiation features associated with either an enterocytelike phenotype or a mucus-secreting phenotype, respectively (13,14). Notably, the mucus-secreting HT29-5M21 clone, selected by resistance to methotrexate, displayed a spontaneous invasive phenotype in a type I collagen layer, whereas parental HT-29 cells are noninvasive under the same conditions (17). Recently, we demonstrated that conditioned medium from HT29-5M21 cells, but not from parental HT-29 cells, induced various colon epithelial cells to invade a collagen layer, supporting a potential role of secreted factor(s) in this spontaneous invasive behavior (18).…”
Section: Introductionmentioning
confidence: 94%
“…We have previously shown that the HT-29-derived subclone 5M21 displayed a constitutive invasive behavior in type I collagen whereas the parental HT-29 STD cells were not spontaneously invasive in this extracellular matrix component (Truant et al, 2003). In order to verify the possibility that this spontaneous invasive behavior could be mediated by autocrine proinvasive factor(s) secreted by HT-29 5M21 cells, we have analysed the proinvasive potential of the conditioned medium (CM) prepared from these cells.…”
Section: Ht-29 5m21 Cells Secrete Autocrine Proinvasive Factor(s)mentioning
confidence: 99%
“…To our knowledge, the possible contribution of TATI in the molecular and cellular mechanisms involved in cancer progression are unknown. We have previously reported that the mucin-secreting cell clone (HT-29 5M21) isolated from a subpopulation of human colon cancer cells HT-29 cells resistant to methotrexate (Lesuffleur et al, 1998) displayed spontaneous cellular self-aggregation and invasive phenotypes in type I collagen gels (Truant et al, 2003). We, therefore, investigated the molecular and cellular mechanisms underlying this aggressive behavior.…”
Section: Introductionmentioning
confidence: 99%